Investigación de mercado para la aceptación de la empresa de capacitación realjobs orientada al sector industrial de Santo Domingo de los Tsáchilas - Herrera Ruano, Carmen Elena (2013)
In Santo Domingo de los Tsáchilas, few consulting companies that provide the service of training, despite being one of the cities of greater industrial growth of the country, that is why there is this market study, it is performed in order to determine the level of acceptance of the training company Realjobs oriented to the industrial sector of Santo Domingo de los Tsáchilas for which this sector needs were analyzed, with respect to services of training aimed at workers, similarly identified firms that operate in the area, which identified the types of training that they provide. To implement the market study, we used several techniques and research instruments, which made possible the collection, interpretation and analysis of the results achieved through the implementation of surveys and interviews, respectively the workers, administrators, area heads and managers of the companies in the industrial sector in Santo Domingo de los Tsáchilas. The results of the study, allowed answer the questions, the objectives and verify the hypothesis that led to capture the respective conclusions and recommendations. Through analysis, it was verified that there is clearly a high degree of acceptance of a training company, offering its services according to the needs of the industrial sector of Santo Domingo de los Tsáchilas, it was found that there are few consulting firms in the area, these offer a limited and poor training service, result is dissatisfaction, which makes feasible the implementation of the province Realjobs training company. With products obtained from market research found that there is the feasibility of implementing efficient advertising strategies for positioning training company Realjobs in the industrial sector of the province of Santo Domingo de los Tsáchilas.